The effect of the housing crisis in the Alabama Black Belt on respiratory health - Newman, Sharlene D.; Akca Sumengen, Aylin; Rasbury, Michael; McDaniel, Steven (Frontiers in Allergy, 2024)
BackgroundThere is a growing housing crisis in rural America with homelessness growing in addition to a growing number of substandard homes due to an inability to afford the costs of repair and maintenance. The goal of the current study was to assess the housing concerns in rural Alabama Black Belt communities which are often understudied and the relationship between housing quality and respiratory health.MethodsA semi-random sampling of five Black Belt counties was conducted to obtain a sample of 253 rural households. The survey was designed to obtain information regarding household income, housing status including a list of safety concerns and respiratory health. A χ2 analysis was performed to examine the effect of housing type and income on prevalence of respiratory illness and safety home concerns (e.g., roofing, windows/doors, floors, mold/mildew).ResultsThe majority of households surveyed had an annual income below 15,000 and owned their homes with over half of the homes being manufactured homes. Lower income was associated with increased prevalence of asthma [χ2(2, N = 237) = 7.75, p = 0.021], while living in a manufactured home was associated with increased risk of allergies [χ2(1, N = 251) = 7.88, p = 0.005]. Additionally, poor windows and doors [χ2(1, N = 253) = 3.8, p = 0.05] was associated with higher prevalence of asthma.ConclusionsThe results confirm and expand previous results and demonstrate the relationship between quality housing and allergy and asthma prevalence in rural areas with an abundance of aging manufactured homes.